Networked Identity Work as Project Development Among Co-Creative Communities - Vivienne Sonja (Cultural Science)
Networked identity work is the conscious negotiation or co-creation of identity, enacted by speaking and listening across differences among multiple publics, including those real and imagined, familiar and unknown, on and offline, present and future. It is a concept I explore extensively in research with queer Digital Storytellers who share their personal stories in public places to catalyse social change (Vivienne 2013). In this article I consider distinctions between ‘story’ and ‘identity’; ‘networking’ and ‘networked identity work’ and argue that the two concepts may be usefully employed in development of co-creative community projects. Finally I consider how variable definitions of co-creativity influence project development.